Comparison of the results of clinical and morphological methods of research in HPV-associated diseases of the cervix (retrospective study) - Djamilya I. Attoeva; Alexandra V. Asaturova; Vera N. Prilepskaya; Nataliia L. Starodubtseva; Polina L. Sheshko; Ada T. Uruymagova (IP Berlin A.V., 2021)
Aim. To conduct a retrospective analysis and evaluate the morphological methods for HPV-related intraepithelial lesions detection in women of reproductive age. Materials and methods. The data of cytological diagnosis, as well as the results of histological reports were analyzed for the period from 2018 to 2019. A comparative analysis was performed in 415 patients with HPV-related intraepithelial lesions, who applied to the scientific and polyclinic department of the Kulakov National Research Medical Center at the age of 19 to 45 years. Morphological examination was carried out by specialists of the 1st pathology department of the Center. Results. According to the results of a comparative analysis of cytological and histological conclusions, 3 groups were formed: 1 the group of coincidence (agree) of cytological and histological conclusions; 2 group of minor discrepancies (minor under/ over) between cytological and histological finding; 3 group of major discrepancies (major under/ over) between cytological and histological findings. Cytological and histological compliance was achieved in 194 (46.74%) patients. The total number of minor nonconformities was 192 (46%) cases. The total number of significant discrepancies between cytological and histological findings was 29 (6.9%) patients: 20 (4.8%) cases were found in the group NILM, hr. cervicitis HSIL and 9 (2.1%) cases in the group HSIL hr. cervicitis according to the results of histological examination. Conclusion. Cervical screening reduces the risk of breast cancer due to cytological examination of the cervix, but histological examination is crucial in making a correct diagnosis, since its result determines the choice of treatment method. The comparative analysis showed that in all groups there were cases of hypo- and hyperdiagnostics during cytological examination although the major discrepancies which can change treatment algorithm, were found only in 6.8% cases.